Two new iridoid glycosides from Callicarpa nudiflora. Issue 3 (3rd March 2020) - Fu, Hui-Zheng; Ma, Yuan-Yu; Ma, Shuang-Cheng; Zhou, Zhi-Qiang; Luo, Yue-Hua
Abstract: Two new iridoid glycosides, callicoside E (1 ) and callicoside F (2 ), were isolated from the leaves of Callicarpa nudiflora . Their structures were established by one- and two-dimensional NMR spectroscopy and mass spectrometry. In an in vitro bioassay, compounds 1 and 2 showed an pronounced hepatoprotective activity against d -galactosamine-induced toxicity in WB-F344 rat hepatic epithelial stem-like cells.